Near-net-shape preparation method of ultrahigh-strength wear-resistant aluminum alloy drill rod
By forming a wear-resistant layer of titanium-aluminum intermetallic compounds and titanium nitride particles on the surface of the aluminum alloy drill rod, the problems of high cost, long process and insufficient plasticity in the preparation of existing aluminum alloy drill rods are solved, and efficient wear resistance improvement and material strengthening are achieved.
Patent Information
- Application Number
- CN202510319888.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-07-04
AI Technical Summary
The existing aluminum alloy drill rod preparation methods have problems such as high preparation cost, long processing flow, and the strength and plasticity cannot be improved synergistically. Especially when the wear resistance is improved by the external ceramic phase, the dispersion and interface bonding strength are poor, and the transition layer structure is difficult to effectively prepare.
Titanium powder and aluminum powder are ball milled under a protective atmosphere, and then composite powder is formed and calcined under a nitrogen atmosphere. Cold isostatically formed to cover the surface of hollow aluminum alloy ingots. Through sintering, a wear-resistant layer of titanium-aluminum intermetallic compounds and titanium nitride particles is formed. Combined with hot extrusion and heat treatment, an ultra-high strength aluminum alloy drill rod is finally prepared.
It improves the wear resistance and bonding strength of aluminum alloy drill rods, enhances the room temperature plasticity and fatigue properties of the material, simplifies the production process, improves the material utilization rate, and is suitable for large-scale industrial production.
Smart Images

Figure CN120243939A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of drill pipe preparation, and particularly relates to a near-net shape preparation method for ultra-high strength wear-resistant aluminum alloy drill pipes. Background Art
[0002] With the development of drilling technology and the increase in the number of deep wells and ultra-deep wells, the mainstream steel drill pipes have problems such as excessive self-weight and insufficient strength margin. Compared with steel drill pipes, aluminum alloy drill pipes have advantages such as high specific strength, non-magnetic property, corrosion resistance, and stable high-strength and tough mechanical properties, and have become the preferred solution for the design of drill pipes in horizontal wells, scientific ultra-deep wells, extended reach wells, and deep earth scientific research.
[0003] However, the surface hardness of aluminum alloy drill pipes is relatively low, about 50 - 60% of that of steel. During the drilling process, they will collide with the wellbore wall, easily resulting in technical defects such as friction wear, scratches, and indentations, causing the aluminum alloy drill pipes to wear and thin, reducing their load-bearing capacity, and thus bringing potential safety hazards in the well.
[0004] Currently, although various methods for preparing high-strength aluminum alloy drill pipes have been developed at home and abroad, there are more or less technical defects among them.
[0005] For example: Chinese Patent CN114345970A discloses a high-strength corrosion-resistant aluminum alloy drill pipe and its preparation method. Although this method can obtain an aluminum alloy drill pipe with a yield strength of up to 600 MPa and corrosion resistance in a salt spray environment, its spray forming process parameters are difficult to control, and the interfacial bonding strength between the Ni60 coating and the aluminum matrix is relatively low. The coating thickness is limited and cannot improve the corrosion resistance and wear resistance of the aluminum alloy drill pipe as a whole.
[0006] Chinese Patent CN106868363A discloses an aluminum alloy drill pipe material and its preparation method, obtaining an aluminum alloy material with good thermal stability. Although the tensile strength at room temperature is greater than 550 MPa, it does not exceed 600 MPa, and the yield ratio is less than 0.93. However, the types of alloying elements are complex, including the addition of high-cost rare earth elements, which easily result in high preparation costs, uneven distribution of components in the prepared material, and easy generation of cracks during the deformation processing, reducing the material yield.
[0007] Chinese Patent CN107043901A discloses a basalt fiber and ceramic particle hybrid aluminum alloy drill pipe material and its preparation method, using the method of rolling ball milling to prepare fiber and particle-reinforced aluminum matrix composites. First, the mass fractions of basalt fibers and ceramic particles added to achieve the required performance of the aluminum alloy drill pipe are relatively high, and it is difficult for rolling ball milling to achieve a uniform dispersion effect. Secondly, basalt fibers are extremely easy to break during the rolling ball milling process, and the ideal fiber strengthening effect cannot be achieved. This method uses vacuum hot pressing sintering and cannot prepare large-sized ingots.
[0008] Chinese Patent CN104561700A discloses a pipe body for a 620 MPa grade aluminum alloy drill pipe and its manufacturing method, which is directed to a 7000 series aluminum alloy with specific components. This method requires multi-stage homogenization treatment, variable cross-section extrusion treatment, double-stage solution treatment, pre-deformation and aging treatment to obtain. Not only is the preparation time cost relatively high and the production process relatively long, but also the upper limit value of the yield strength of the prepared pipe body material is lower than the lower limit value of this application.
[0009] Chinese Patent CN108278088A discloses a steel-aluminum gradient composite drill pipe and its preparation method. The drill pipe structure is designed as an inner and outer double-layer structure. The outer layer and joint part of the drill pipe are made of steel, and the inner layer part is made of aluminum alloy. The interface between the steel and the aluminum alloy is achieved through a transition layer with a proportional gradient change between the two. Obviously, the transition layer is generally divided into 9 layers and has a relatively thin thickness. During the printing process, due to the laser melting method, the components of the upper transition layer will be mixed with the components of the lower transition layer, and it is difficult to obtain a transition layer with a gradient change. The printing cost is high and the practicability is poor.
[0010] Therefore, there is an urgent need to develop a low-cost and short-process manufacturing technology for aluminum alloy drill pipes with high strength and wear resistance and high bonding strength of the wear-resistant layer. Summary of the Invention
[0011] The technical problem to be solved by the present invention is that most of the current preparations of wear-resistant aluminum alloy drill pipes improve the surface hardness of aluminum alloy drill pipes and enhance the friction and wear performance by surface spraying, deposition, and preparation of new composite materials. However, these technical solutions have technical defects such as high preparation cost, long processing flow, and inability to synergistically improve strength and plasticity. Especially when improving wear resistance by adding ceramic phases externally, its dispersibility and interfacial bonding strength play a crucial role in the performance of the composite material, which is also a major problem restricting the development of new composite materials. In addition, there are also attempts to improve the comprehensive performance through the design of the drill pipe structure, but there are technical defects such as difficulty in effectively preparing the transition layer structure and poor structural bonding ability.
[0012] To solve the above technical problems, the technical solutions provided by the present invention are as follows:
[0013] A near-net-shape preparation method for a super-high-strength wear-resistant aluminum alloy drill pipe, the near-net-shape preparation method for the super-high-strength wear-resistant aluminum alloy drill pipe comprises the following steps:
[0014] S1. Ball-mill and mix titanium powder and aluminum powder under a protective atmosphere to obtain a mixed powder, and calcine the mixed powder under a nitrogen atmosphere to obtain a composite powder;
[0015] S2. Select aluminum alloy powder for drill pipes. After ball-milling the aluminum alloy powder, load it into a U-shaped silica gel sheath with a hollow inner diameter of 5 - 50 cm at the core and a sandwich thickness of 100 - 300 cm, and cold isostatically press it into a hollow aluminum alloy circular ingot.
[0016] S3. Place the hollow aluminum alloy ingot from S2 at the center of a U-shaped silica gel sheath with the same hollow inner diameter at the core and a sandwich thickness increased by 5 - 10 cm. Then, fill the composite powder from S1 around the hollow aluminum alloy ingot. After vibration compaction and evacuation, cold isostatically press it again to form an aluminum alloy hollow composite ingot.
[0017] S4. Sinter and densify the aluminum alloy hollow composite ingot from S3 to obtain a sintered ingot.
[0018] S5. Hot-extrude the sintered ingot from S4 to obtain a fully dense wear-resistant aluminum alloy hollow pipe.
[0019] S6. Heat-treat the fully dense wear-resistant aluminum alloy hollow pipe from S5, and then through machining, finally obtain an ultra-high strength and toughness aluminum alloy drill pipe with a wear-resistant layer.
[0020] Optionally, the average particle size of the titanium powder in S1 is 2 - 10 μm, and its shape is irregular; the average particle size of the aluminum powder is 20 - 50 μm, and its shape is spherical; among them, the mass fraction of the titanium powder is 40 - 60 wt.%, and the rest is aluminum powder.
[0021] Optionally, the calcination of the mixed powder in S1 in a nitrogen atmosphere is carried out in two-step heating. The first-step heating is low-temperature heating and insulation, with a temperature of 600 - 800 °C and a time of 2 - 4 h to form titanium-aluminum intermetallic compounds; the second-step heating is high-temperature heating and insulation, with a temperature of 800 - 1200 °C and a time of 2 - 4 h to form titanium nitride wear-resistant particles.
[0022] Optionally, the titanium-aluminum intermetallic compounds in S1 are near-spherical particles with a size of 1 - 10 μm, and the titanium nitride particles are spherical with a size of 500 nm - 1 μm.
[0023] Optionally, the ball-milling methods in S1 and S2 include rolling ball-milling, vibration ball-milling, and planetary ball-milling. The ball-milling time is 5 - 20 h, the ball-to-material ratio is between 3:1 and 10:1, and the ball-milling atmosphere is one or two of nitrogen, argon, and other protective atmospheres.
[0024] Optionally, the aluminum alloy powder in S2 is 7075 aluminum alloy powder, 7055 aluminum alloy powder, or 7085 aluminum alloy powder, with an average particle size of 10 - 50 μm; the hollow aluminum alloy circular ingot is formed by low-pressure cold isostatic pressing, with a pressure of 100 - 200 MPa and a time of 60 - 300 s.
[0025] Optionally, the size of the central hole in the center of the silica gel sheath in S3 is the same as that in S2, and the inner diameter of the outer circle is increased by 2 - 10 cm compared to S2; the filling standard for the composite powder is to be vibrated and evacuated; and cold isostatic pressing adopts a stepped pressure-holding strategy: the first-level pressure-holding pressure is 100 - 200 MPa, and the time is 60 - 300 s; the second-level pressure-holding pressure is 200 - 300 MPa, and the time is 60 - 300 s.
[0026] Optionally, the sintering densification in S4 is one or more of vacuum sintering and atmosphere protection sintering.
[0027] Optionally, the sintering densification in S4 is vacuum sintering. First, it is kept at 200 - 350 °C for 0.5 - 3 h, then heated to the sintering temperature at a heating rate of 5 - 10 °C / min. The sintering temperature is 450 - 630 °C, and the holding time is 2 - 20 h. After that, it is cooled to room temperature with the furnace. The overall density of the sintered ingot is 90 - 99.5%.
[0028] Optionally, the temperature of hot extrusion in S5 is 300 - 400 °C, and the extrusion ratio is 9:1 - 16:1.
[0029] Optionally, the heat treatment in S6 adopts the T6 heat treatment process. The solution treatment temperature is 450 - 490 °C, the holding time is 1 - 5 h, and water quenching is carried out; the artificial aging temperature is 120 - 150 °C, the holding time is 12 - 48 h, and air cooling is carried out.
[0030] Optionally, if other conditions remain unchanged and the particle sizes of pure aluminum powder and pure titanium powder decrease from large to small, then the wear resistance of the finally prepared aluminum alloy drill pipe gradually improves.
[0031] Optionally, if other conditions remain unchanged and the particle size of the aluminum alloy powder decreases from large to small, then among the properties of the finally prepared aluminum alloy drill pipe, the tensile strength, yield strength, elongation, and fatigue life gradually increase.
[0032] Optionally, the thickness of the wear-resistant layer is 0.68 - 0.75 cm. Two wear-resistant phases, titanium-aluminum intermetallic compound and titanium nitride particles, are dispersedly distributed on the surface and subsurface of the aluminum alloy drill pipe. The titanium-aluminum intermetallic compound is in the shape of near-spherical particles with a size of 1 - 10 μm, and the titanium nitride particles are spherical with a size of 500 nm - 1 μm. The bonding strength between the wear-resistant layer and the matrix material is 50 - 80 MPa.
[0033] Optionally, as the thickness of the wear-resistant layer increases, the bonding strength between the wear-resistant layer and the matrix material slightly decreases, the average friction weight loss significantly weakens, and the hardness significantly increases.
[0034] Optionally, the obtained ultra-high strength and toughness aluminum alloy drill pipe with a wear-resistant layer has a tensile strength of 672 - 810 MPa, a yield strength of 643 - 780 MPa, a yield ratio of 0.95 - 0.97, and an elongation of 8 - 12%; the room temperature tensile strength after thermal exposure at 150 °C for 500 h is 650 - 710 MPa, the yield strength is 610 - 680 MPa, and the elongation is 10 - 15%; the surface hardness is 350 - 450 HV.
[0035] The above technical solution has at least the following beneficial effects compared with the prior art:
[0036] The present invention provides a near-net shape preparation method for ultra-high strength and wear-resistant aluminum alloy drill pipes, which can solve the technical problems in the prior art such as long preparation process, uneven structure, high cost, low material utilization rate, poor strength and toughness, and poor wear resistance of aluminum alloy drill pipes, broaden the application range of aluminum alloy drill pipes, and facilitate industrial production.
[0037] The present invention obtains titanium-aluminum intermetallic compound and titanium nitride composite powder by means of segmented heating, then cold isostatically presses and forms it on the surface of an aluminum alloy hollow ingot, and finally forms a wear-resistant layer with a two-phase synergistic effect on the ingot surface through sintering diffusion to improve the wear resistance of the aluminum alloy drill pipe.
[0038] For the powder metallurgy aluminum alloy hollow ingot of the present invention, after ball milling, the oxide layer on the surface of these aluminum powders is broken into nano-aluminum oxide strengthening phases with excellent high-temperature stability, which can inhibit dynamic recovery and recrystallization during subsequent processing, maintain a fine grain structure, and improve the hot working performance; it can also hinder the movement of dislocations, increase the material strength, and produce an obvious dispersion strengthening effect.
[0039] The thickness of the wear-resistant layer prepared by the present invention is 0.68 - 0.75 cm, and the two wear-resistant phases of titanium-aluminum intermetallic compound and titanium nitride particles act synergistically to increase the wear resistance of the aluminum alloy drill pipe.
[0040] The obtained ultra-high strength and toughness aluminum alloy drill pipe with a wear-resistant layer has a tensile strength of 672 - 810 MPa, a yield strength of 643 - 780 MPa, a yield ratio of 0.95 - 0.97, and an elongation of 8 - 12%; the room temperature tensile strength after thermal exposure at 150 °C for 500 h is 650 - 710 MPa, the yield strength is 610 - 680 MPa, and the elongation is 10 - 15%; the hardness is 350 - 450 HV.
[0041] In summary, compared with other traditional methods, the method of the present invention greatly improves the bonding strength and wear resistance of the wear-resistant layer of the prepared aluminum alloy drill pipe by surface sintering titanium aluminide intermetallic compound and titanium nitride wear-resistant layer. Through the powder metallurgy ball milling process combined with the cold isostatic pressing near-net-shape technology, the aluminum alloy drill pipe prepared has excellent properties such as room temperature plasticity, strength, and fatigue performance. The production process flow is short, the material utilization rate is high, which is conducive to large-scale industrial production and popularization and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.
[0043] Figure 1 It is a working flow chart of a near-net-shape preparation method for an ultra-high wear-resistant aluminum alloy drill pipe of the present invention;
[0044] Figure 2 It is a microstructural diagram of the surface section of the drill pipe prepared by the near-net-shape preparation method for an ultra-high wear-resistant aluminum alloy drill pipe in Embodiment 1 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0045] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the following will clearly and completely describe the technical solutions of the embodiments of the present invention with reference to the drawings of the embodiments of the present invention. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the described embodiments of the present invention without creative efforts belong to the scope of protection of the present invention.
[0046] A near-net-shape preparation method for an ultra-high strength and wear-resistant aluminum alloy drill pipe, the near-net-shape preparation method for the ultra-high strength and wear-resistant aluminum alloy drill pipe combines Figure 1 The following steps:
[0047] S1. Ball-mill and mix titanium powder and aluminum powder under a protective atmosphere to obtain a mixed powder, and calcine the mixed powder under a nitrogen atmosphere to obtain a composite powder;
[0048] S2. Select aluminum alloy powder with the composition of the drill pipe, ball-mill the aluminum alloy powder and then load it into a U-shaped silica gel jacket with a hollow inner diameter of 5 - 50 cm at the core and a sandwich thickness of 100 - 300 cm, and cold isostatically press it into a hollow aluminum alloy circular ingot;
[0049] S3. Place the hollow aluminum alloy ingot of S2 at the center of a U-shaped silica gel sleeve with a consistent inner diameter of the hollow center and an increased sandwich thickness of 5 - 10 cm. Then, fill the composite powder of S1 around the hollow aluminum alloy ingot. After vibration compaction and evacuation, perform cold isostatic pressing again to obtain an aluminum alloy hollow composite ingot.
[0050] S4. Sinter and densify the aluminum alloy hollow composite ingot of S3 to obtain a sintered ingot.
[0051] S5. Perform hot extrusion on the sintered ingot of S4 to obtain a fully dense wear-resistant aluminum alloy hollow pipe.
[0052] S6. Perform heat treatment on the fully dense wear-resistant aluminum alloy hollow pipe of S5, and then through machining, finally obtain an ultra-high strength and toughness aluminum alloy drill pipe with a wear-resistant layer.
[0053] Particularly, the average particle size of the titanium powder in S1 is 2 - 10 μm, and the shape is irregular; the average particle size of the aluminum powder is 20 - 50 μm, and the shape is spherical; among them, the mass fraction of the titanium powder is 40 - 60 wt.%, and the rest is aluminum powder.
[0054] Particularly, the calcination of the mixed powder in S1 in a nitrogen atmosphere is carried out in two-step heating calcination. The first-step heating calcination is low-temperature heating and heat preservation, with a temperature of 600 - 800 °C and a time of 2 - 4 h to form titanium-aluminum intermetallic compounds; the second-step heating calcination is high-temperature heating and heat preservation, with a temperature of 800 - 1200 °C and a time of 2 - 4 h to form titanium nitride wear-resistant particles.
[0055] Particularly, the titanium-aluminum intermetallic compounds in S1 are near-spherical particles with a size of 1 - 10 μm, and the titanium nitride particles are spherical with a size of 500 nm - 1 μm.
[0056] Particularly, the ball milling methods in S1 and S2 include rolling ball milling, vibration ball milling, and planetary ball milling. The ball milling time is 5 - 20 h, the ball-to-material ratio is between 3:1 and 10:1, and the ball milling atmosphere is one or two of nitrogen, argon, and other protective atmospheres.
[0057] Particularly, the aluminum alloy powder in S2 is 7075 aluminum alloy powder, 7055 aluminum alloy powder, or 7085 aluminum alloy powder, with an average particle size of 10 - 50 μm; the hollow aluminum alloy circular ingot is formed by low-pressure cold isostatic pressing, with a pressure of 100 - 200 MPa and a time of 60 - 300 s.
[0058] Specifically, the size of the central hole in the center of the silica gel sheath in S3 is the same as that in S2, and the inner diameter of the outer circle increases by 2 - 10 cm compared to S2; the filling standard of the composite powder is to be vibrated and evacuated; and cold isostatic pressing adopts a stepped pressure-holding strategy: the first-stage pressure-holding pressure is 100 - 200 MPa, and the time is 60 - 300 s; the second-stage pressure-holding pressure is 200 - 300 MPa, and the time is 60 - 300 s.
[0059] Specifically, the sintering densification in S4 is one or more of vacuum sintering and atmosphere protection sintering.
[0060] Specifically, the sintering densification in S4 is vacuum sintering. First, it is held at 200 - 350 °C for 0.5 - 3 h, then heated to the sintering temperature at a heating rate of 5 - 10 °C / min. The sintering temperature is 450 - 630 °C, the holding time is 2 - 20 h, and then it is cooled to room temperature with the furnace. The overall density of the sintered ingot is 90 - 99.5%.
[0061] Specifically, the temperature of hot extrusion in S5 is 300 - 400 °C, and the extrusion ratio is 9:1 - 16:1.
[0062] Specifically, the heat treatment in S6 adopts the T6 heat treatment process. The solution treatment temperature is 450 - 490 °C, the holding time is 1 - 5 h, and it is water quenched; the artificial aging temperature is 120 - 150 °C, the holding time is 12 - 48 h, and it is air cooled.
[0063] Specifically, if other conditions remain unchanged and the particle sizes of the pure aluminum powder and the pure titanium powder decrease from large to small, then the wear resistance of the finally prepared aluminum alloy drill pipe gradually improves.
[0064] Specifically, if other conditions remain unchanged and the particle size of the aluminum alloy powder decreases from large to small, then among the properties of the finally prepared aluminum alloy drill pipe, the tensile strength, yield strength, elongation, and fatigue life gradually increase.
[0065] Specifically, the thickness of the wear-resistant layer is 0.68 - 0.75 cm. Two wear-resistant phases, titanium aluminide intermetallic compound and titanium nitride particles, are dispersedly distributed on the surface and subsurface of the aluminum alloy drill pipe. The titanium aluminide intermetallic compound is in the shape of near-spherical particles with a size of 1 - 10 μm, and the titanium nitride particles are spherical with a size of 500 nm - 1 μm. The bonding strength between the wear-resistant layer and the matrix material is 50 - 80 MPa.
[0066] Specifically, as the thickness of the wear-resistant layer increases, the bonding strength between the wear-resistant layer and the matrix material slightly decreases, the average friction weight loss significantly weakens, and the hardness significantly increases.
[0067] Specifically, the obtained ultra-high strength and tough aluminum alloy drill pipe with a wear-resistant layer has a tensile strength of 672 - 810 MPa, a yield strength of 643 - 780 MPa, a yield ratio of 0.95 - 0.97, and an elongation of 8 - 12%; the tensile strength at room temperature after thermal exposure at 150 °C for 500 h is 650 - 710 MPa, the yield strength is 610 - 680 MPa, and the elongation is 10 - 15%; the surface hardness is 350 - 450 HV.
[0068] Example 1
[0069] A near-net shape preparation method for an ultra-high strength and wear-resistant 7075 aluminum alloy drill pipe, and the near-net shape preparation method for the ultra-high strength and tough 7075 aluminum alloy drill pipe comprises the following steps:
[0070] S1. Spherical pure titanium powder with an average particle size of 10 μm and pure aluminum powder with an average particle size of 25 μm are placed in a stainless steel ball milling tank in a nitrogen atmosphere according to a mass ratio of 3:2 for low-speed ball milling and mixing. The ball-to-material ratio is 3:1, the rotation speed of ball milling is 60 r / min, and the ball milling time is 5 h to finally obtain mixed powder; then the mixed powder is subjected to two-step heating and calcination in a nitrogen atmosphere to obtain composite powder, which includes titanium aluminide intermetallic compound and titanium nitride wear-resistant particles: the first step of heating and calcination is low-temperature calcination and heat preservation at a temperature of 700 °C for 3 h to form titanium aluminide intermetallic compound with a near-spherical shape and a size of 5 - 8 μm; the second step is high-temperature calcination and heat preservation at a temperature of 1000 °C for 3 h to form titanium nitride wear-resistant particles with a spherical shape and a size of 500 - 800 nm;
[0071] S2. Ball mill 7075 aluminum alloy powder with a particle size of 20 μm, with a ball-to-material ratio of 9:1, a rotation speed of ball milling of 120 r / min, and a ball milling time of 5 h to break the surface oxide film of the aluminum powder to form a nano-aluminum oxide dispersion strengthening phase; then the 7075 aluminum alloy powder is filled into a hollow silica gel sleeve and cold isostatically pressed to obtain a hollow aluminum alloy circular ingot, where the pressure of cold isostatic pressing is 150 MPa and the pressure holding time is 100 s;
[0072] S3. Place the hollow aluminum alloy circular ingot of S2 in a hollow sleeve with a larger inner diameter (the size of the central hole of the sleeve is the same as that of S2, and the inner diameter of the outer circle is 2 cm larger than that of S2), and then evenly fill the composite powder prepared in S1 around the hollow aluminum alloy circular ingot, vibrate and evacuate, where the filling standard of the composite powder is vibration and evacuation; then adopt a hierarchical pressure holding strategy for cold isostatic pressing and forming: the first-stage pressure holding pressure is 150 MPa and the time is 60 s; the second-stage pressure holding pressure is 300 MPa and the time is 300 s to obtain an aluminum alloy hollow composite ingot;
[0073] S4. Place the aluminum alloy hollow composite ingot obtained in S3 into a vacuum sintering furnace. First, keep it at 300 °C for 2 h, then increase the temperature to the sintering temperature of 600 °C at a heating rate of 5 °C / min, keep the temperature for 5 h, and then cool it to room temperature with the furnace to obtain a sintered ingot with a relative density of 95.5%.
[0074] S5. Perform hot extrusion on the sintered ingot obtained in S4 at an extrusion temperature of 370 °C and an extrusion ratio of 9:1 to obtain a fully dense wear-resistant aluminum alloy hollow pipe.
[0075] S6. Perform heat treatment on the fully dense wear-resistant aluminum alloy hollow pipe obtained in S5, and then through machining, finally obtain an ultra-high strength and toughness aluminum alloy drill pipe with a wear-resistant layer. Among them: the heat treatment adopts the T6 heat treatment process, the solution treatment temperature is 480 °C, the holding time is 2 h, and water quenching is carried out; the artificial aging temperature is 120 °C, the holding time is 24 h, and air cooling is carried out.
[0076] In this embodiment, the thickness of the wear-resistant layer is 0.72 cm. As Figure 2 shown, two wear-resistant phases, titanium aluminide intermetallic compound and titanium nitride particles, are dispersed. The first step of heating and calcining is low-temperature calcining and holding, the temperature is 700 °C, and the time is 3 h to form titanium aluminide intermetallic compounds, which are nearly spherical in shape and 5 - 8 μm in size; the second step is high-temperature calcining and holding, the temperature is 1000 °C, and the time is 3 h to form titanium nitride wear-resistant particles, which are spherical in shape and 500 - 800 nm in size; the bonding strength between the wear-resistant layer and the matrix material is 80 MPa.
[0077] In this embodiment, with the increase of the thickness of the wear-resistant layer, the bonding strength between the wear-resistant layer and the matrix material decreases slightly, the average friction weight loss decreases significantly, and the hardness increases significantly.
[0078] In this embodiment, the obtained ultra-high strength and toughness aluminum alloy drill pipe with a wear-resistant layer has a tensile strength of 672 MPa, a yield strength of 643 MPa, a yield ratio of 0.957, and an elongation of 11.6%; the room-temperature tensile strength after thermal exposure at 150 °C for 500 h is 653 MPa, the yield strength is 621 MPa, and the elongation is 14.2%; the surface hardness is 389 HV.
[0079] In this embodiment, if other conditions remain unchanged and the particle sizes of pure aluminum powder and pure titanium powder decrease from large to small, then the wear resistance of the finally prepared aluminum alloy drill pipe gradually increases.
[0080] In this embodiment, if other conditions remain unchanged and the particle size of aluminum alloy powder decreases from large to small, then among the properties of the finally prepared aluminum alloy drill pipe, the tensile strength, yield strength, elongation, and fatigue life gradually increase.
[0081] Example 2
[0082] Near-net shape preparation method of an ultra-high strength and wear-resistant 7055 aluminum alloy drill pipe. The near-net shape preparation method of the ultra-high strength and tough 7055 aluminum alloy drill pipe comprises the following steps:
[0083] S1. Spherical pure titanium powder with an average particle size of 2 μm and pure aluminum powder with an average particle size of 20 μm are placed in a stainless steel ball milling tank in a nitrogen atmosphere according to a mass ratio of 1:1 for low-speed ball milling and mixing. The ball-to-material ratio is 5:1, the rotation speed of ball milling is 80 r / min, and the ball milling time is 5 h to finally obtain a mixed powder. Then, the mixed powder is subjected to two-step heating and calcination in a nitrogen atmosphere to obtain a composite powder, which includes titanium-aluminum intermetallic compounds and titanium nitride wear-resistant particles: The first step of heating and calcination is low-temperature calcination and heat preservation at a temperature of 600 °C for 2 h to form titanium-aluminum intermetallic compounds with a near-spherical shape and a size of 1-5 μm; the second step is high-temperature calcination and heat preservation at a temperature of 1200 °C for 3 h to form titanium nitride wear-resistant particles with a spherical shape and a size of 800 nm-1 μm;
[0084] S2. 7055 aluminum alloy powder with a particle size of 25 μm is ball milled with a ball-to-material ratio of 5:1, a rotation speed of ball milling of 100 r / min, and a ball milling time of 10 h to break the surface oxide film of the aluminum powder to form a nano-aluminum oxide dispersion strengthening phase. Then, the 7055 aluminum alloy powder is filled into a hollow silica gel sleeve and cold isostatically pressed to obtain a hollow aluminum alloy circular ingot, where the pressure of cold isostatic pressing is 150 MPa and the pressure holding time is 200 s;
[0085] S3. The hollow aluminum alloy circular ingot of S2 is placed in a hollow sleeve with a larger inner diameter (the size of the central hole of the sleeve is the same as that of S2, and the inner diameter of the outer circle increases by 5 cm compared with S2). Then, the composite powder prepared in S1 is uniformly filled around the hollow aluminum alloy circular ingot, vibrated and evacuated. Among them, the filling standard of the composite powder is vibration and evacuation. Then, a cold isostatic pressing forming is carried out by using a stepwise pressure holding strategy: the first-stage pressure holding pressure is 180 MPa and the time is 100 s; the second-stage pressure holding pressure is 200 MPa and the time is 300 s to obtain an aluminum alloy hollow composite ingot;
[0086] S4. The aluminum alloy hollow composite ingot of S3 is placed in a vacuum sintering furnace, first kept at 400 °C for 2 h, then heated to a sintering temperature of 580 °C at a heating rate of 5 °C / min, and the heat preservation time is 5 h. Then, it is cooled to room temperature with the furnace to obtain a sintered ingot with a relative density of 92.5%;
[0087] S5. The sintered ingot of S4 is subjected to hot extrusion at an extrusion temperature of 370 °C and an extrusion ratio of 16:1 to obtain a fully dense wear-resistant aluminum alloy hollow pipe;
[0088] S6. Heat-treat the fully dense wear-resistant aluminum alloy hollow pipe of S5, and then perform machining to finally obtain an ultra-high strength and toughness aluminum alloy drill pipe with a wear-resistant layer. Among them: The heat treatment adopts the T6 heat treatment process. The solution treatment temperature is 480°C, the holding time is 2 h, and water quenching is carried out. The artificial aging temperature is 120°C, the holding time is 24 h, and air cooling is carried out.
[0089] In this embodiment, the thickness of the wear-resistant layer is 0.68 cm. Two wear-resistant phases, titanium aluminide intermetallic compound and titanium nitride particles, are dispersedly distributed. The first-step heating and calcination is low-temperature calcination and heat preservation, the temperature is 600°C, and the time is 2 h to form titanium aluminide intermetallic compounds, whose shape is near spherical and the size is 1 - 5 μm. The second step is high-temperature calcination and heat preservation, the temperature is 1200°C, and the time is 3 h to form titanium nitride wear-resistant particles, whose shape is spherical and the size is 800 nm - 1 μm. The bonding strength between the wear-resistant layer and the matrix material is 68 MPa.
[0090] In this embodiment, as the thickness of the wear-resistant layer increases, how does the bonding strength between the wear-resistant layer and the matrix material change, and how do the average friction weight loss and hardness change?
[0091] In this embodiment, the tensile strength of the finally obtained ultra-high strength and toughness aluminum alloy drill pipe with a wear-resistant layer is 755 MPa, the yield strength is 728 MPa, the yield ratio is 0.964, and the elongation is 11.6%. After thermal exposure at 150°C for 500 h, the room-temperature tensile strength is 704 MPa, the yield strength is 677 MPa, and the elongation is 12.5%. The hardness is 425 HV.
[0092] In this embodiment, if other conditions remain unchanged and the particle sizes of pure aluminum powder and pure titanium powder change from large to small, then the wear resistance of the finally prepared aluminum alloy drill pipe gradually increases.
[0093] In this embodiment, if other conditions remain unchanged and the particle size of the aluminum alloy powder changes from large to small, then among the properties of the finally prepared aluminum alloy drill pipe, the tensile strength, yield strength, elongation, and fatigue life gradually increase.
[0094] Example 3
[0095] A near-net-shape preparation method for an ultra-high strength and wear-resistant 7085 aluminum alloy drill pipe. The near-net-shape preparation method for the ultra-high strength and toughness 7085 aluminum alloy drill pipe is as follows:
[0096] S1. Place spherical pure titanium powder with an average particle size of 5 μm and pure aluminum powder with an average particle size of 50 μm in a stainless steel ball milling tank under a nitrogen atmosphere in a mass ratio of 3:2 for low-speed ball milling and mixing. The ball-to-material ratio is 5:1, the rotation speed of ball milling is 100 r / min, and the ball milling time is 5 h to finally obtain a mixed powder. Then, the mixed powder is subjected to two-step heating and calcination in a nitrogen atmosphere to obtain a composite powder, which includes titanium-aluminum intermetallic compounds and titanium nitride wear-resistant particles: The first step of heating and calcination is low-temperature calcination and heat preservation at a temperature of 800 °C for 2 h to form titanium-aluminum intermetallic compounds, which are nearly spherical in shape and have a size of 5 - 10 μm. The second step is high-temperature calcination and heat preservation at a temperature of 1200 °C for 2 h to form titanium nitride wear-resistant particles, which are 800 nm - 1 μm in shape.
[0097] S2. Ball mill 7085 aluminum alloy powder with a particle size of 45 μm. The ball-to-material ratio is 10:1, the rotation speed of ball milling is 120 r / min, and the ball milling time is 6 h to achieve the purpose of breaking the surface oxide film of the aluminum powder to form a nano-aluminum oxide dispersion strengthening phase. Then, the 7085 aluminum alloy powder is filled into a hollow silica gel sleeve and cold isostatically pressed to obtain a hollow aluminum alloy circular ingot. The pressure of cold isostatic pressing is 150 MPa, and the pressure holding time is 100 s.
[0098] S3. Place the hollow aluminum alloy circular ingot of S2 in a hollow sleeve with a larger inner diameter (the size of the central hole of the sleeve is the same as that of S2, and the inner diameter of the outer circle increases by 8 cm compared with S2). Then, uniformly fill the composite powder prepared in S1 around the hollow aluminum alloy circular ingot, vibrate and evacuate. Among them, the filling standard of the composite powder is vibration and evacuation. Then, use a hierarchical pressure holding strategy for cold isostatic pressing and forming: The first-stage pressure holding pressure is 150 MPa, and the time is 60 s; the second-stage pressure holding pressure is 300 MPa, and the time is 300 s to obtain an aluminum alloy hollow composite ingot.
[0099] S4. Place the aluminum alloy hollow composite ingot of S3 in a vacuum sintering furnace. First, keep it at 300 °C for 2 h, then heat it up to the sintering temperature of 610 °C at a heating rate of 5 °C / min, and keep it at this temperature for 5 h. Then, cool it to room temperature with the furnace to obtain a sintered ingot with a relative density of 91.7%.
[0100] S5. Perform hot extrusion on the sintered ingot of S4 at an extrusion temperature of 370 °C and an extrusion ratio of 25:1 to obtain a fully dense wear-resistant aluminum alloy hollow pipe.
[0101] S6. Perform heat treatment on the fully dense wear-resistant aluminum alloy hollow pipe of S5, and then through machining, finally obtain an ultra-high strength and toughness aluminum alloy drill pipe with a wear-resistant layer. Among them: The heat treatment adopts the T6 heat treatment process. The solution treatment temperature is 480 °C, the heat preservation time is 2 h, and water quenching is carried out. The artificial aging temperature is 120 °C, the heat preservation time is 24 h, and air cooling is carried out.
[0102] In this embodiment, the thickness of the wear-resistant layer is 0.75 cm. Two wear-resistant phases, titanium aluminide intermetallic compound and titanium nitride particles, are dispersed. The first step of heating and calcining is low-temperature calcination and heat preservation at a temperature of 800 °C for 2 h to form titanium aluminide intermetallic compounds, which are nearly spherical in shape and have a size of 5 - 10 μm. The second step is high-temperature calcination and heat preservation at a temperature of 1200 °C for 2 h to form titanium nitride wear-resistant particles, which are spherical in shape and have a size of 800 nm - 1 μm. The bonding strength between the wear-resistant layer and the matrix material is 72 MPa.
[0103] In this embodiment, as the thickness of the wear-resistant layer increases, how does the bonding strength between the wear-resistant layer and the matrix material change, and how do the average friction weight loss and hardness change?
[0104] In this embodiment, the tensile strength of the ultra-high strength and tough aluminum alloy drill pipe with a wear-resistant layer is 723 MPa, the yield strength is 706 MPa, the yield ratio is 0.9664, and the elongation is 12%. After thermal exposure at 150 °C for 500 h, the room-temperature tensile strength is 695 MPa, the yield strength is 671 MPa, and the elongation is 14.1%. The hardness is 413 HV.
[0105] In this embodiment, if other conditions remain unchanged and the particle sizes of pure aluminum powder and pure titanium powder decrease from large to small, then the wear resistance of the finally prepared aluminum alloy drill pipe gradually improves.
[0106] In this embodiment, if other conditions remain unchanged and the particle size of the aluminum alloy powder decreases from large to small, then among the properties of the finally prepared aluminum alloy drill pipe, the tensile strength, yield strength, elongation, and fatigue life gradually increase.
[0107] For the above scheme, the present invention proposes a near-net-shape preparation method for ultra-high strength and wear-resistant aluminum alloy drill pipes, which can solve the technical problems in the prior art such as long preparation process, uneven structure, high cost, low material utilization rate, poor strength and toughness, and poor wear resistance of aluminum alloy drill pipes, broaden the application range of aluminum alloy drill pipes, and facilitate industrial production.
[0108] The present invention obtains titanium aluminide intermetallic compound and titanium nitride composite powder by means of segmented heating, then cold isostatically presses and forms it on the surface of an aluminum alloy hollow ingot, and finally forms a wear-resistant layer with a two-phase synergistic effect on the surface of the ingot through sintering diffusion to improve the wear resistance of the aluminum alloy drill pipe.
[0109] For the powder metallurgy aluminum alloy hollow ingot of the present invention, after ball milling, the oxide layer on the surface of these aluminum powders is broken into nano-aluminum oxide strengthening phases with excellent high-temperature stability, which can inhibit dynamic recovery and recrystallization during subsequent processing, maintain a fine grain structure, and improve the hot working performance; it can also hinder the movement of dislocations, increase the material strength, and produce an obvious dispersion strengthening effect.
[0110] The wear-resistant layer prepared by the present invention has a thickness of 0.68 - 0.75 cm. The two wear-resistant phases of titanium-aluminum intermetallic compound and titanium nitride particles act synergistically to increase the wear resistance of the aluminum alloy drill pipe.
[0111] The ultra-high strength and toughness aluminum alloy drill pipe with a wear-resistant layer prepared by the present invention has a tensile strength of 672 - 810 MPa, a yield strength of 643 - 780 MPa, a yield ratio of 0.95 - 0.97, and an elongation of 8 - 12%; the room-temperature tensile strength after thermal exposure at 150 °C for 500 h is 650 - 710 MPa, the yield strength is 610 - 680 MPa, and the elongation is 10 - 15%; the hardness is 350 - 450 HV.
[0112] In summary, compared with other traditional methods, the method of the present invention significantly improves the bonding strength and wear resistance of the wear-resistant layer of the prepared aluminum alloy drill pipe by surface sintering of titanium-aluminum intermetallic compound and titanium nitride wear-resistant layer. Through the powder metallurgy ball milling process combined with the cold isostatic pressing near-net shape technology, the aluminum alloy drill pipe prepared has excellent properties such as room-temperature plasticity, strength, and fatigue performance. The production process flow is short, the material utilization rate is high, which is conducive to large-scale industrial production and popularization and use.
[0113] The above is the preferred embodiment of the present invention. It should be pointed out that for those of ordinary skill in the art of this technology, without departing from the principle described in the present invention, several improvements and refinements can still be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A near-net shape preparation method for an ultra-high strength and wear-resistant aluminum alloy drill pipe, characterized in that, The near-net shape preparation method of the ultra-high strength wear-resistant aluminum alloy drill pipe is as follows: S1. Mix titanium powder and aluminum powder by ball milling under a protective atmosphere to obtain a mixed powder, and calcine the mixed powder under a nitrogen atmosphere to obtain a composite powder; S2. Select aluminum alloy powder with the composition of the drill pipe, ball mill the aluminum alloy powder and then load it into a U-shaped silica gel sleeve with a hollow inner diameter of 5 - 50 cm at the core and a sandwich thickness of 100 - 300 cm, and cold isostatically press it into a hollow aluminum alloy circular ingot; S3. Place the hollow aluminum alloy ingot in S2 at the center of a U-shaped silica gel sleeve with the same hollow inner diameter at the core and a sandwich thickness increased by 5 - 10 cm. Then fill the composite powder in S1 around the hollow aluminum alloy ingot, compact it and evacuate it, and then cold isostatically press it again to form an aluminum alloy hollow composite ingot; S4. Sinter and densify the aluminum alloy hollow composite ingot in S3 to obtain a sintered ingot; S5. Hot extrude the sintered ingot in S4 to obtain a fully dense wear-resistant aluminum alloy hollow pipe; S6. Heat-treat the fully dense wear-resistant aluminum alloy hollow pipe in S5, and then through machining, finally obtain an ultra-high strength and tough aluminum alloy drill pipe with a wear-resistant layer.
2. The near-net shape preparation method of the ultra-high strength wear-resistant aluminum alloy drill pipe according to claim 1, characterized in that, The average particle size of the titanium powder in S1 is 2 - 10 μm, and the shape is irregular; the average particle size of the aluminum powder is 20 - 50 μm, and the shape is spherical; among them, the mass fraction of the titanium powder is 40 - 60 wt.%, and the rest is aluminum powder.
3. The near-net shape preparation method of the ultra-high strength wear-resistant aluminum alloy drill pipe according to claim 1, characterized in that, The calcination of the mixed powder in S1 under a nitrogen atmosphere is carried out in two steps of heating and calcination. The first step of heating and calcination is low-temperature heating and heat preservation, the temperature is 600 - 800 °C, and the time is 2 - 4 h to form titanium-aluminum intermetallic compounds; the second step of heating and calcination is high-temperature heating and heat preservation, the temperature is 800 - 1200 °C, and the time is 2 - 4 h to form titanium nitride wear-resistant particles.
4. The near-net shape preparation method of the ultra-high strength wear-resistant aluminum alloy drill pipe according to claim 1, characterized in that, The ball milling methods in S1 and S2 include rolling ball milling, vibration ball milling and planetary ball milling, the ball milling time is 5 - 20 h, the ball-to-material ratio is between 3:1 and 10:1, and the ball milling atmosphere is one or two of nitrogen, argon and other protective atmospheres.
5. The near-net shape preparation method of the ultra-high strength wear-resistant aluminum alloy drill pipe according to claim 1, characterized in that, The aluminum alloy powder in S2 is 7075 aluminum alloy powder, 7055 aluminum alloy powder or 7085 aluminum alloy powder, and the average particle size is 10 - 50 μm; the hollow aluminum alloy circular ingot is formed by low-pressure cold isostatic pressing, the pressure is 100 - 200 MPa, and the time is 60 - 300 s.
6. The near-net shape preparation method of the ultra-high strength wear-resistant aluminum alloy drill pipe according to claim 1, characterized in that, The size of the central hole in the center of the silica gel sleeve in S3 is the same as that in S2, and the outer circle inner diameter is 2 - 10 cm larger than that in S2; the filling standard of the composite powder is to be compacted and evacuated; and the cold isostatic pressing adopts a step-by-step pressure holding strategy: the first-level pressure holding pressure is 100 - 200 MPa, and the time is 60 - 300 s; the second-level pressure holding pressure is 200 - 300 MPa, and the time is 60 - 300 s.
7. The near-net shape preparation method of the ultra-high strength wear-resistant aluminum alloy drill pipe according to claim 1, characterized in that The sintering densification in S4 is one or more of vacuum sintering and atmosphere protection sintering.
8. The near-net shape preparation method of the ultra-high strength wear-resistant aluminum alloy drill pipe according to claim 1, characterized in that, The sintering densification in S4 is vacuum sintering. First, keep the temperature at 200 - 350 °C for 0.5 - 3 h, then increase the temperature to the sintering temperature at a heating rate of 5 - 10 °C / min, the sintering temperature is 450 - 630 °C, the heat preservation time is 2 - 20 h, and then cool it to room temperature with the furnace. The overall density of the sintered ingot is 90 - 99.5%.
9. The near-net shape preparation method of the ultra-high strength wear-resistant aluminum alloy drill pipe according to claim 1, characterized in that, The temperature of hot extrusion in S5 is 300 - 400 °C, and the extrusion ratio is 9:1 - 16:
1.
10. The near-net shape preparation method of the ultra-high strength wear-resistant aluminum alloy drill pipe according to claim 1, characterized in that, In S6, the heat treatment adopts the T6 heat treatment process. The solution treatment temperature is 450 - 490 °C, the holding time is 1 - 5 h, followed by water quenching; the artificial aging temperature is 120 - 150 °C, the holding time is 12 - 48 h, followed by air cooling.
Citation Information
Patent Citations
Pipe body for 620MPa aluminum alloy drill pipe and manufacturing method of pipe body
CN104561700A
Aluminum alloy drill pipe material and preparation method thereof
CN106868363A
Basalt fiber and ceramic particle mixed aluminum alloy drill rod material and preparation method thereof
CN107043901A
Steel-aluminum gradient composite material drilling rod and preparation method thereof
CN108278088A
High-strength corrosion-resistant aluminum alloy drill rod and preparation method thereof
CN114345970A
Cited By
Online quenching 7075 ultrahigh-strength aluminum alloy seamless pipe as well as preparation and application of online quenching 7075 ultrahigh-strength aluminum alloy seamless pipe
CN121538528A